Gender-Technology Relations - Corneliussen, H. author. aut Link
VII, 203 p.
Keywords: Through empirical material as well as theoretical discussions, this book explores developments in gender-technology relations from the 1980s to today. The author draws on her long-lasting research in the field, providing insight in both historical and more recent discussions of gender in relation to computers and computing.